BANKRUPTCY OF NATURAL PERSONS IN LITHUANIA: ISSUES AND SOLUTIONS - Tamosiuniene, Egidija; Terebeiza, Zilvinas; Bolzanas, Darius (European Scientific Journal, ESJ, 2013)
This article deals with the issues related to the implementation of the Law on the Bankruptcy of Natural Persons which came into force in Lithuania on 1 March 2013. The authors briefly discuss the nature and essence of bankruptcy of natural persons as a social phenomenon, and explore the problematic issues that are likely to come up in the practice of Lithuanian courts when applying the provisions of the Law on Bankruptcy of Natural Persons in specific stages of these proceedings.